Against a Single Story: Diverse Trans* Narratives in Autobiographical Documentary Film. (2nd January 2019) - Rondot, Sarah Ray
Abstract: In opposition to the sensational, simplified, and pathological gender ideologies in twentieth and early twenty-first century documentary film, Jules Rosskam's Against a Trans Narrative [Rosskam, Jules., dir. Against a Trans Narrative . 2008; Chicago, IL: MamSir Productions. DVD.] and Gwen Tara Haworth's She's a Boy I Knew [Haworth, Gwen Tara, dir. She's a Boy I Knew. 2008; Durham, England: Shapeshifter Films. DVD.] expand representational horizons for autobiographical trans* narratives films. Rather than risking their stories' re-appropriation by cisgender directors and editors, trans* documentarians are increasingly telling their own gender stories.